To simplify the given expression \( \frac{4^0 \cdot 5^{-2}}{(-2)^{-3}} \) using the properties of integer exponents, follow these steps:
-
Simplify \(4^0\): Any non-zero number raised to the power of 0 is 1. Thus, \(4^0 = 1\).
\[ \frac{1 \cdot 5^{-2}}{(-2)^{-3}} \]
-
Rewrite \(5^{-2}\): According to the negative exponent rule, \(a^{-n} = \frac{1}{a^n}\). So,
\[ 5^{-2} = \frac{1}{5^2} = \frac{1}{25} \]
Now we can update our expression:
\[ \frac{1/25}{(-2)^{-3}} \]
-
Rewrite \((-2)^{-3}\): Similarly,
\[ (-2)^{-3} = \frac{1}{(-2)^3} = \frac{1}{-8} \]
Now we can rewrite the expression:
\[ \frac{1/25}{1/(-8)} = \frac{1}{25} \cdot \frac{-8}{1} = \frac{-8}{25} \]
-
Final simplified result:
\[ \frac{-8}{25} \]
Thus, the final answer is:
\[ \frac{-8}{25} \]